Some effect of 2, 3, 5 -Triiodobenzoic acid and indol -3- acetic acid on the absorption and distribution of iron by plants - Jiménez Saenz, Eduardo (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The influence of TIBA & LAA on nutrient utilization by coffee and cocoa seedlings grown in nutrient solution was investigated under different conditions, and the following findings were found: